Load-velocity behaviour during the first and second pull of the snatch and clean - Patterson, E. L.; Ahn, N.; Kipp, K. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of the study was to examine the effect of barbell load on the velocity during the first and second pull of the snatch and clean. Fifteen elite weightlifters (M= 6, F = 9) performed multiple repetitions of the snatch and clean at 75%-100% of their one-repetition max. Load-velocity (L-V) regression models were created for the first pull and second pull for each of the two lifts. The slopes of the L-V relationships were extracted from each model to determine how load affects each pull of the corresponding lifts. The results suggested that the L-V slopes for the snatch (p = 0.006) and clean (p = 0.015) differed between the first and second pull. For the snatch, the L-V slopes were greater during the second pull, whereas the opposite was true for the clean. Interestingly, differences in L-V slopes during the snatch were less pronounced in weaker lifters.